"Beyond Personal Beliefs": Italian Health Care Providers' Self-Perception of Their Own Job Attitudes and Reflections on the Contraceptive Behaviors of Adolescent Patients. (October 2016) - Olivari, Maria Giulia; Cuccì, Gaia; Confalonieri, Emanuela
Using a qualitative method, our study aims to explore, identify, and describe Italian health care providers' reflections on the contraceptive behaviors of adolescents attending family health centers, and health care providers' self-perception of their own job attitudes toward these adolescent patients. Semi-structured interviews with 46 Italian health care providers were conducted and analyzed using thematic analysis. Two main themes emerged from the thematic data analysis regarding Italian health care providers' self-perceptions and reflections. The first main theme was labeled "adolescents' contraceptive behavior" and included two subthemes: "adolescents are confused and unprepared" and "contraception is a girls' responsibility." The second theme was labeled "job attitudes with adolescents, " and included three subthemes: "to inform and to educate, " "to build trustful relationships, " and "to go beyond personal beliefs." The findings of this study showed that Italian health care providers perceive themselves as nonjudgmental and they interpret their own behavior as an attempt to answer adolescents' sexual and reproductive health (SRH) needs in an open-minded way. Their work with adolescent patients with relation to contraceptive behaviors is led by the desire to educate through building a significant and long-term relationship that could sustain these patients.